ANALISIS SITIRAN DAN KETERSEDIAAN SKRIPSI PROGRAM STUDI SASTRA INDONESIA TAHUN 2019-2021 DI PERPUSTAKAAN UNIVERSITAS NEGERI PADANG - Ahmad Ramasya Fuad; Ardoni Ardoni (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2022)
The limited collection as a source of information in compiling a research framework is a problem that is often faced by students, so the library must evaluate the collection to find out how the collection is used by the user. There are several methods that can be used to evaluate library collections, one of which is to use citation analysis. The purpose of this study is to describe the characteristics of literature based on type, language of instruction, author, title, and half life) and its availability in the UNP Library. This research is a quantitative research with descriptive method. The population in this study were 105 Indonesian Literature UNP students' thesis for 2019 - 2021 and the sample used was 40 theses. The instrument in this study was the use of collection recording tables. Data collection was carried out using the documentation method through a list of citation data fields. Data analysis used the percentage formula and interpreted with percentage criteria then made a cumulative frequency distribution table and then calculated the half life of the literature. The results of this study were that the book was the most cited type of collection at 64.2%, the most cited book title was Qualitative Research Methodology at 19.3%, the most frequently cited journal was the Language and Literature Journal published by Padang State University 39.4%, the most-cited author is Hasanuddin WS as much as 11.4%, the most-cited language is Indonesian 98.8%, the half-life of a book is 14 years, the half-life of a journal is 12 years and the collection utilization rate is The Padang State University Library in the 2019-2021 Indonesian Literature thesis is 66.7% available literature and 33.3% unavailable literature. It can be concluded that the level of utilization of the collections of the Padang State University Library in Indonesian Literary Thesis 2019-2021 is high.